STRENGTHENING LEGAL PROTECTION AGAINST WOMEN TRADE CASE (HUMAN TRAFFICKING) IN THE CITY OF PALEMBANG - Suryati, Suryati (Jurnal Dosen Universitas PGRI Palembang)
ABSTRACTAlthough according to the data released by the women agency protection such as the Womens Crisis Center (WCC) of Palembang had mentioned that cases of violence and trafficking in women till the end of 2016 has decreased, but strengthening legal protection is still needed since women trade case (Human Trafficking) like an iceberg whose base is in the form of a report. This paper aims to provide an overview of the efforts to strengthen the legal protection against women trafficking case (HumanTrafficking) in Palembang. The method used in this study is normative empirical method. There are three steps that can be done in strengthening of the legal protection towards women trade case (Human Trafficking) in Palembang. They are (1) The draft or design of KUHP (the draft of Criminal Code), (2) Comparative Study/Comparative, and (3) Protection of Victims of women trafficking case by using International standard.Keywords: Legal Protection, Women Trafficking